Design and development of an android-based cognitive assessment application for children with special needs: An educational solution in riverbank areas - Yuwono, Imam (COPE: Caraka Olah Pikir Edukatif, 2025)
The education of children with special needs in remote areas, such as riverbanks, faces various challenges, including limited access to adequate cognitive assessments. This study was a Research and Development (R&D) study involving children with special needs (ABK) residing in riverbank areas and educators working in these environments as research subjects. Data collection in this study was conducted through interviews and observations of children with special needs (ABK) and teachers in the riverbank areas. This study aims to develop an Android-based cognitive assessment application that can be accessed offline, specifically designed for individuals with autism spectrum disorder (ASD) in areas with limited infrastructure. The application development method employed was Research and Development (R&D), including user needs analysis, interface design, development, and application testing by users. The test results show that this application is effective in conducting cognitive assessments, with an automatic reporting feature that makes it easier for teachers and parents to monitor children's development. The offline mode feature allows assessments to be carried out without a stable internet connection. This study concludes that this application has successfully improved access and quality of cognitive assessment for children with special needs in remote areas and has the potential to be implemented in other areas with similar conditions, improving inclusive education for children with special needs.